2012
DOI: 10.1016/j.janxdis.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Gender, gender roles, and anxiety: Perceived confirmability of self report, behavioral avoidance, and physiological reactivity

Abstract: Despite the well-documented gender effect in anxiety, less is known about contributing factors to women's greater risk for anxiety and fears. The present study examined the relationship between gender, gender role orientation (i.e., expressivity/instrumentality) and fear of harmless insects (tarantula), using a multimodal approach of self-report measures, a Behavioral Approach Test (BAT), and physiological reactivity. Participants (144 college students; 67 women, 77 men) completed a questionnaire packet and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 36 publications
3
39
4
Order By: Relevance
“…Although self-reports of fear and anxiety are correlated negatively with masculinity and positively with femininity [59], studies which control for gender role still find a significant effect of biological sex in self-reports [117]. In a behavioural task in which some participants were told that their self-report of fear was verifiable by heart rate monitors, the significant sex difference in fear ratings was unaffected [104]. While social and cultural expectations about gender are important, it appears that they cannot fully explain sex differences in self-reported emotional experience.…”
Section: (D) Anterior Cingulate and Anterior Insula Corticesmentioning
confidence: 98%
See 1 more Smart Citation
“…Although self-reports of fear and anxiety are correlated negatively with masculinity and positively with femininity [59], studies which control for gender role still find a significant effect of biological sex in self-reports [117]. In a behavioural task in which some participants were told that their self-report of fear was verifiable by heart rate monitors, the significant sex difference in fear ratings was unaffected [104]. While social and cultural expectations about gender are important, it appears that they cannot fully explain sex differences in self-reported emotional experience.…”
Section: (D) Anterior Cingulate and Anterior Insula Corticesmentioning
confidence: 98%
“…Sex differences in self-reported and behavioural measures of fear are not matched by differences in sympathetic nervous system reactivity. When fear is induced through incremental behavioural approach to spiders [104], inhalation of CO 2 -enriched air [105], affective images [106], scary movie clips [107] or emotional imagery [108], sex differences in heart rate and blood pressure are not found. In the HPA system, evidence indicates somewhat higher salivary cortisol measures in men after experimental stress induction [109].…”
Section: (C) Amygdala -Peripheral Connectionsmentioning
confidence: 99%
“…Insects can evoke a sense of distress, fear, anxiety, increased heart rate, and impairment in functioning for some individuals (Stoyanova and Hope 2012). For example, head lice do not transmit disease yet can be a cause of considerable mental and social distress (Chunge et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It cannot be excluded that, in a larger sample, an association of benzodiazepine use disorder with the genotypes investigated here might reach significance for women as well. Furthermore, research focusing on gender differences and social desirability in self-reported anxiety suggests an underreporting of fear and distress in men (41)(42)(43). Therefore, our use of three self-reported measures in the calculation of the anxiety composite score might partly explain the lack of association of the BAIAP3 risk genotypes with anxiety in men.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%